The Strategic Role of K.H. Muh. Nuh Khaeruddin in The Dynamics of Islamic Education at Al-Furqan Ereng-ereng Islamic Boarding School, Bantaeng (1986–2004) - Iqmal; Mastanning; Akasa (Al-Hikmah, 2025)
This is a writing of the contributions of KH. Muh. Nuh Khaeruddin in the development of the Al-Furqan Ereng-Ereng Islamic Boarding School, Bantaeng Regency, from 1986 to 2004. The main objectives of this research are to detail the biography of KH. Muh. Nuh Khaeruddin, trace the history of the founding of the Al-Furqan Ereng-Ereng Islamic Boarding School, and analyze the contributions of KH. Muh. Nuh Khaeruddin to the school’s development. This research employs a qualitative descriptive analysis method, utilizing both library and field data. The primary field data source was obtained through interviews, while the library data were collected from various relevant sources. The research approach encompasses historical, educational, religious, and anthropological perspectives. The research steps include heuristics, source criticism, interpretation, and historiography. The results of this research are as follows: First, KH. Muh. Nuh Khaeruddin was born in the village of Ereng-Ereng, Bantaeng, on June 6, 1940. His notable works include the book "Al-Tashrif," the book "Mahu Al-Ibadah," and guidelines for Zakat and Fasting. Second, the history of the Al-Furqan Ereng-Ereng Islamic Boarding School began with the return of KH. Muh. Nuh Khaeruddin to his hometown to promote Islamic education. In 1986, he founded the Al-Furqan Ereng-Ereng Islamic Boarding School. Third, KH. Muh. Nuh Khaeruddin’s focus on deepening religious knowledge had a positive impact on the students, leading to the development of a cadre of preachers to continue his missionary efforts. Implications: The author hopes that this thesis will be useful for readers to learn about KH. Muh. Nuh Khaeruddin, a scholar who significantly influenced the development of Islamic education, particularly at the Al-Furqan Ereng-Ereng Islamic Boarding School in Bantaeng Regency. Future researchers are recommended to discuss in more detail the development of Islamic boarding schools influenced by KH. Muh. Nuh Khaeruddin’s thinking.